2017
DOI: 10.1111/1750-3841.13920
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Arabinoxylan Isolation from Rye Bran by Adapting Extraction Solvent and Use of Enzymes

Abstract: Physicochemical and functional properties of arabinoxylans (AXs) can be significantly influenced by their isolation method. Finding balanced process conditions that allow optimal extraction yields while preserving AXs functionality is a challenge. The aim of this study was to determine the effect of different chemical solvents with neutral and alkaline pH on the intrinsic properties and extraction yield of AXs isolated from rye bran. Additionally, the application of xylanases and other cell wall degrading enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…e composition of each concentrate varied significantly amongst arabinoxylans, and therefore, different functionalities in the GF batter were expected. Especially, FA might favor cross-linking to a different degree, but also other properties such as their branching degree (A/X ratio), molecular weight, and the presence of coextracted impurities (i.e., glucose and dextrins, protein, and other dietary fiber components) might determine their behavior in the bread batter as reported in earlier studies [3,8].…”
Section: Arabinoxylan Extractionmentioning
confidence: 88%
See 3 more Smart Citations
“…e composition of each concentrate varied significantly amongst arabinoxylans, and therefore, different functionalities in the GF batter were expected. Especially, FA might favor cross-linking to a different degree, but also other properties such as their branching degree (A/X ratio), molecular weight, and the presence of coextracted impurities (i.e., glucose and dextrins, protein, and other dietary fiber components) might determine their behavior in the bread batter as reported in earlier studies [3,8].…”
Section: Arabinoxylan Extractionmentioning
confidence: 88%
“…Previous research has already confirmed that extraction parameters (solvents, pH, or temperature) significantly modify the chemical and functional properties of AXs, which in turn affect the rheological behavior of gluten-free batters [8,9]. eir effect will closely depend not only on the type and concentration of AX added but also on the selection of GF flour and the presence of oxidants in the batter [3].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…These properties were derived from Bender et al (2018b), except for the starch content, which was calculated by differences. Rye AX was extracted with calcium hydroxide following the procedure of Bender et al (2017b) and POx was recombinantly expressed from the white rot fungus Phanerochaete chrysosporium and purified, as explained by Spadiut et al (2010). A commercial GF rice-based sourdough starter culture (Böcker Reinzucht-Sauerteig-Reis) was purchased from Ernst Böcker GmbH & Co (Minden, Germany).…”
Section: Methodsmentioning
confidence: 99%